Antecedents of corporate reputation with employees in higher education institutions: a systematic review. Issue 1 (4th January 2021) - Rashid, Sufyan; Mustafa, Hasrina
Abstract : Purpose: The purpose of this paper is to provide a systematic review of studies on antecedents of the corporate reputation of higher education institutions (HEIs) from the perspectives of employees Design/methodology/approach: The approach is an examination of previous literature on antecedents of corporate reputation in HEIs, published between 2010 and 2020. Findings: The findings show that general and specific factors of corporate reputation in HEIs are being employed as strategic tools to survive the competitive nature of the higher education landscape. Originality/value: Factors of corporate reputation in HEIs from the perspectives of employees are an understudied area with little academic literature available.